1990
DOI: 10.1002/jlb.48.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Development, Differentiation, and Maturation of Macrophages in the Fetal Mouse Liver

Abstract: Primitive macrophages emerged in the sinusoidal lumen of the fetal mouse liver at 10 days of gestation before the initiation of hepatic hematopoiesis and matured into fetal macrophages. In the culture of cell suspensions from the fetal liver with LP3-conditioned medium, monocyte colonies were formed, but monocytopoiesis was poor in the early stage of hepatic hematopoiesis in vivo. In the culture of cell suspensions obtained from the fetal liver at 10 days of gestation on the monolayer of a mouse bone marrow st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 29 publications
2
76
0
1
Order By: Relevance
“…We found erythroblasts clustered around the sinusoidal macrophages. In adult livers, sinusoidal macrophages are distributed primarily in the peripheral region of hepatic lobules [Naito et al, 1990]. As shown in figure 4 a, the same results were obtained in the F4/80-immunostained sections.…”
Section: Discussionsupporting
confidence: 74%
“…We found erythroblasts clustered around the sinusoidal macrophages. In adult livers, sinusoidal macrophages are distributed primarily in the peripheral region of hepatic lobules [Naito et al, 1990]. As shown in figure 4 a, the same results were obtained in the F4/80-immunostained sections.…”
Section: Discussionsupporting
confidence: 74%
“…Fetal immature macrophages are observed in the subepidermal mesenchyme in rats at embryonic day 12, and it is reported that macrophages in the resident population possess phagocytic vesicles in the cytoplasm at embryonic day 18 (Takahashi et al, 1983). Monocytes appear in the blood at embryonic day 17 in mice, and monocyte-derived macrophages show peroxidase activity at the end of the embryonic period (Naito et al, 1990). In our study, macrophages were present in newborn mice and phagocytized dying olfactory neurons.…”
mentioning
confidence: 68%
“…But in vitro studies indicate that not only the yolk sac but also the embryo itself exhibits hematopoietic precursors which have the potential to differentiate into myeloid cells (Huang et al, 1994;Cumano et al, 1996). Nevertheless, the first appearance and clonal proliferation of immature macrophages have been described in the blood islands of mouse and rat yolk sac around day 9 (Cline and Moore, 1972;Takahashi et al, 1989;Naito et al, 1990a), and after the connection between the vitelline vessels and the embryonic cardiovascular system around fetal day 10, the first mature fetal macrophages were visible throughout embryonic mesenchymal tissue (Takahashi et al, 1989, Naito et al, 1990b). As we described here, Mts1-expressing macrophages were first noted 2 days later, around day 12 of gestation.…”
Section: Mts1 Is Expressed In Fetal Macrophages During Mouse Developmentmentioning
confidence: 99%